Card Sort Learning Strategy for Enhancing Islamic Education Motivation: A Qualitative Study in Indonesian Madrasah Context - Rahmawati Rahmawati; Norhana Annisa; Mustapa Ahmad (Journal of Contemporary Islamic Primary Education, 2025)
Despite numerous studies examining active learning strategies in religious education, limited research explores contextual implementation of card sort methodology in Indonesian Islamic primary schools (madrasah), particularly regarding student motivation enhancement. This study investigates the implementation of card sort learning media in Aqidah Akhlak (Islamic Creed and Ethics) instruction at Madrasah Ibtidaiyah Negeri 7 Hulu Sungai Selatan, Indonesia. Employing qualitative descriptive methodology, data were collected through semi-structured interviews, classroom observations, and documentation analysis following Miles and Huberman's analytical framework. Findings reveal three critical implementation phases: (1) systematic planning utilizing the ASSURE model encompassing learner analysis, objective formulation, method selection, media utilization, learner participation, and evaluation; (2) execution involving preliminary, core, and closing activities designed to foster interactive and engaging learning environments; (3) comprehensive evaluation combining authentic assessment and written examinations. Results demonstrate significant improvements in student learning outcomes, evidenced by enhanced conceptual understanding (78% increase in comprehension scores) and practical application of moral values in daily contexts. This study contributes empirical evidence supporting active learning strategies in Islamic education, offering practical implications for curriculum designers and educators seeking to improve religious instruction quality in Southeast Asian educational contexts while advancing Sustainable Development Goal 4 (Quality Education).